ANALYSING SEGMENTING, TARGETING, AND POSITIONING TO FORMULATE GLOBAL MARKETING STRATEGY FOR ASAHAN’S OPAK CRACKERS - Fathan Ariq; Nailul Muna; Nurhaliza; Rhama Fahrezy Syumantra; Suhairi (International Journal Labs, 2022)
This study aims to determine the analysis of Segmenting, Targeting and Positioning to Formulate Asahan's